Mechanism of phosphinidene complex arylation by arylboronic acids - Ng, Yong Xiang (2014)
The arylation reaction of terminal phosphinidene complexes [RP-W(CO)5] by arylboronic acids is very sensitive to steric hindrance and the electronic properties of the substituents on the aryl ring. On the basis of DFT calculations and additional experiments, it seems that the mechanism involves first an insertion of the phosphinidene into one of the B–O bonds, followed by an intramolecular nucleophilic attack of the aryl group onto the P–OH bond promoted by the potassium phosphate. The [1,2]-aryl shift from B to P cannot be reproduced with an alkyl group.